2021
DOI: 10.1080/03056244.2020.1865902
|View full text |Cite
|
Sign up to set email alerts
|

Struggles over value: corporate–state suppression of locally led mining mechanisation in the Democratic Republic of the Congo

Abstract: The analytical framework deployed by the extensive Global Value Chain (GVC) literature on African mining fails to consider how and from whom value is transferred within the process of establishing foreign corporate-led mining GVCs, and with what consequences. We explore these questions through a case study of the gold value chain in the Democratic Republic of the Congo. In this context, we argue that a coalition between transnational capital and the Congolese state has marginalised and held back locally-led pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It could also become more important if the focus shifted from the extraction of resources to their local transformation. The degree of mechanisation also has an effect; the best option for local employment would probably be limited and locally led mechanisation (see for example Radley and Geenen, 2021). Regarding plantations, the cash crop economies of West Africa have shown that free small-scale farming can be an efficient alternative that has the potential to generate relevant income (Cooper, 1996).…”
Section: Conclusion For Social Policies and Theorymentioning
confidence: 99%
“…It could also become more important if the focus shifted from the extraction of resources to their local transformation. The degree of mechanisation also has an effect; the best option for local employment would probably be limited and locally led mechanisation (see for example Radley and Geenen, 2021). Regarding plantations, the cash crop economies of West Africa have shown that free small-scale farming can be an efficient alternative that has the potential to generate relevant income (Cooper, 1996).…”
Section: Conclusion For Social Policies and Theorymentioning
confidence: 99%
“…Local producers in the Global South, often overpowered by the interests of transnational corporations and governmental pressures could therefore have easy access to such technology. For example, in the Democratic Republic of the Congo, a coalition between transnational capital and the Congolese state has held back locally led processes of mining mechanisation [30]. Access to simple, modular, and regenerative technology such as SMDR could empower local producers to process and scale-up mining output locally.…”
Section: A Regenerative Approach For Resilient Manufacturingmentioning
confidence: 99%
“…Radley & Vogel, 2015 for a critique of this “conflict minerals” paradigm). The focus here and in the sections that follow is instead and deliberately placed on the Congolese workers, managers, and traders operating locally, predominantly at and around the mines, and who, in the case of gold, capture around 90–95% of the total value generated by productive activity (Radley & Geenen, 2021, p. 166).…”
Section: Historicizing the Emergence Of Asgm In South Kivumentioning
confidence: 99%
“…361–362). As documented by Radley and Geenen (2021), by deploying the Congolese state's judicial and security apparatus to protect its deposits, Banro has acted to repress and undermine ASGM mechanization efforts, including by cutting down electricity pylons and having the mining authorities appropriate many of the ball mills in operation in Kamituga and ban their use in the corporation's most strategically valuable deposits. This recalls one of the major findings from MacGaffey's (1987, p. 213) earlier ethnography of local class formation and struggle in Kisangani and North Kivu of the DRC that “so far the state has certainly not played a crucial role in assisting the formation of the local capitalist class and mediating its relationship with foreign capital.” On the contrary, in the case of ASGM in South Kivu more than 30 years later, the state has functioned to actively undermine and repress the aspirations and trajectory of this local capitalist class.…”
Section: Social Stratificaton and Capital Accumulationmentioning
confidence: 99%
See 1 more Smart Citation